Salmonella enterica Serotype Typhi Bacteremia Complicating Pregnancy in the Third Trimester - George F. Guirguis; Krunal Patel; Lisa Gittens-Williams; Joseph J. Apuzzio; Kristina Martimucci; Shauna F. Williams (Hindawi Limited, 2017)
Background. Salmonella enterica serotype Typhi (S. Typhi) is an anaerobic gram-negative enteric rod that causes infection when contaminated food or water is ingested and may cause illness in pregnancy. Case. This is a patient who presented at 31 weeks' gestation with abdominal pain and fever and was diagnosed with S. Typhi bacteremia. Conclusion. S. Typhi should be considered in febrile patients with recent travel presenting with abdominal discomfort with or without elevated liver enzymes.